Core ionization initiates subfemtosecond charge migration in the valence shell of molecules - Kuleff, Alexander I.; Kryzhevoi, Nikolai V.; Pernpointner, Markus; Cederbaum, Lorenz S. (Physical review letters, 2016)
After the ionization of a valence electron, the created hole can migrate ultrafast from one end of the molecule to another. Because of the advent of attosecond pulse techniques, the measuring and understanding of charge migration has become a central topic in attosecond science. Here, we pose the hitherto unconsidered question whether ionizing a core electron will also lead to charge migration. It is found that the created hole in the core stays put, but in response to this hole interesting electron dynamics takes place which can lead to intense charge migration in the valence shell. This migration is typically faster than that after the ionization of a valence electron and transpires on a shorter time scale than the natural decay of the core hole by the Auger process, making the subject very challenging to attosecond science.
Gesehen am 03.06.2020